A scoping functionalist reflections on the implementation of affirmative action in Higher Education Institutions in South Africa - Zwelendaba, Thokoza; Obioha, Emeka E. (Universitas PGRI Madiun, 2024)
The scoping review was carried out to investigate the functionalist perspective on affirmative action for women in the workplace in the Eastern Cape Province’s selected South African universities. Given that university-specific information is available on affirmative action for women in the workplace, this scoping review employed a systematic review to investigate the implementation of the legislative framework for affirmative action policy in African-selected universities and ways to make improvements. Purposive sampling was used to select four higher education institutions (HEIs), in which there were two historically black and two historically white institutions, for representativeness. Evidently, affirmative action is indeed an existing policy in the selected institutions to redress the exclusion of women in senior positions in the past. While this review revealed the heightened visibility of women in executive positions in the four universities, women tend to be represented more than men in some executive categories. This demonstrates that the implementation of affirmative action for women has largely been successful in the country. Although with some challenges, the inclusion of women, without gender discrimination and biases, is a necessary ingredient for the sustainability of higher education administration in the country from a functionalist perspective.